Evaluación de buenas prácticas agrícolas en el cultivo tomate de árbol (Solanum betaceum cav.), Parroquia Mulalillo, Cantón Salcedo, Provincia de Cotopaxi 2019- 2020. - Manobanda Ichina, Mayra Cristina (2020)
The present research was carried out in the property of Mr. Marcelo Mayorga located in the Salcedo canton, Mulalillo Parish, Cunchibamba Chico neighborhood, with the objective of evaluating the compliance of good agricultural practices in the cultivation of tamarillo. The field methodology and documentary literature were used, the techniques were direct observation and the checklist obtained from Resolution 108 of Agrocalidad and the manual of good agricultural practices for Agrocalidad tree Tomato. To conduct the investigation, a GPS was used to determine the geographical location of the property. The initial audit was conducted where the results informed us that there is incomplete information about the UPA, soil, fertilizer management, chemicals, harvest, post-harvest storage and traceability. It was recommended to correct each of these points, a new audit was carried out to corroborate the solutions that were proposed, and some information records were implemented regarding the UPA, cutlivo, fertilization, plant health, harvest, post-harvest, storage, handling Environmental and traceability. Of the collection of information in the risk matrix in the production of tree tomato were: 1 moderate risk, 14 important risks and 5 intolerable risks, the BPA should be applied to the cultivation of tree tomato to control a healthy and harmless product and in the same way precautionary with the health of the workers, taking care of the environment and complying with the established norms and thus having a competitive product an added value. Finally, the owner was informed so that the certification of good agricultural practices for the cultivation of tamarillo can be requested from the Competent Authority